The coldest girl in Coldtown [compact disc, unabridged] - Black, Holly (Hachette Audio, 2013)
When seventeen-year-old Tana wakes up following a party in the aftermath of a violent vampire attack, she travels to Coldtown, a quarantined Massachusetts city full of vampires, with her ex-boyfriend and a mysterious vampire boy in tow.